2021
DOI: 10.3390/ma15010177
|View full text |Cite
|
Sign up to set email alerts
|

Laser Remelting Process Simulation and Optimization for Additive Manufacturing of Nickel-Based Super Alloys

Abstract: Nickel-based super alloys are popular for applications in the energy and aerospace industries due to their excellent corrosion and high-temperature resistance. Direct metal deposition (DMD) of nickel alloys has reached technology readiness for several applications, especially for the repair of turbomachinery components. However, issues related to part quality and defect formation during the DMD process still persist. Laser remelting can effectively prevent and repair defects during metal additive manufacturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Laser remelting melts coarse columnar grains, inhibits grain growth, and results in a more uniform composition distribution, optimizing the alloy's microstructure, reducing surface roughness, and improving mechanical properties such as wear and corrosion resistance [49][50][51]. In general, there are two types of laser remelting treatments, surface remelting and interlayer remelting, with surface remelting applied only to the last layer of the part.…”
Section: Laser Remeltingmentioning
confidence: 99%
“…Laser remelting melts coarse columnar grains, inhibits grain growth, and results in a more uniform composition distribution, optimizing the alloy's microstructure, reducing surface roughness, and improving mechanical properties such as wear and corrosion resistance [49][50][51]. In general, there are two types of laser remelting treatments, surface remelting and interlayer remelting, with surface remelting applied only to the last layer of the part.…”
Section: Laser Remeltingmentioning
confidence: 99%
“…The temperature fields were simulated numerically with the Comsol Multiphysics 6.1 software. Two different models were developed for the calculation of these, differing only in that, in one model, the melt pool flow was considered and, in the other, it was not, in order to achieve a higher computational efficiency, as mentioned in Soffel et al [26]. Detailed information on the simulation approach is described in Wirth and Wegener [27] and can be taken from there.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Simulation tools can also be used to simplify the procedure for process parameters’ determination in AM. Soffel et al [ 24 ] performed the optimization of remelting process parameters for part repair in DED via numerical simulation. The models predicted the melt pool shape, and they concluded that the optimized remelting parameters increased the bonding quality between the base and deposited materials.…”
Section: Introductionmentioning
confidence: 99%